HEFESTDROID: Highly Effective Features for Android Malware Detection and Analysis - et.al, Shafiu Musa (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Rapid globalization and advances in mobile technology have brought about phenomenal attention and great opportunities for android application developers to contribute meaningfully to the global digital market. The android mobile platform being one of the famous mobile operating systems has the highest number of applications in the digital market with a total market share of 76.23% between August 2018 and August 2019, according to a report of global stats counter. However, the substantial number of applications on the platform has led to a great number of malware attacks on the user’s privacy and sensitive documents. Consequently, a significant number of malware detection studies have been carried out to reduce the number of malware attacks. This paper analyses the impact of using highly effective android permission features to decipher the problem malware attack. The Highly Effective Features for Android Malware Detection and Analysis (HEFEST) summarises four effective android permission features to be considered in conducting malware detection analysis and classifications. The features recognized in this study are; Normal Declared Permission, Dangerous Permission, Signature-Based Permission, and Signature-or-system. The selection is based on the capabilities of the features in depicting the behaviors of android apps. The research data are drawn from Drebin open source, the dataset comprises 15,036 benign and malicious applications extracted from 215 distinct features, the records 9,026 were malicious and 6,010 benign applications. However, this research compares the detection accuracy of android permission features using machine learning-based algorithms; Support Vector Machine, and K-Nearest Neighbor to achieve a comprehensive accuracy ratio of malware detection, the classifier has a strong accuracy decision of classification and exceptional computational efficiency. The model correctly classified 2,812 out of 2,869 malicious applications appropriately with an accuracy of 98.0% and also classified 1,607 out of 1,642 accurately with a success rate of 97.9%. Generally, 98.0% of classification accuracy was archived.